Monoclonal Antibodies as Cancer Therapeutics - Han, MD, PhD, Jiawen (North American Journal of Medicine and Science, 2010)
Monoclonal antibodies have emerged as key therapeutic modalities for a range of human diseases. Owing to selective targetting of these agents on tumor cells, cancer has become one of the major focuses for development of monoclonal antibody therapeutics. The most significant breakthroughs in the development of monoclonal antibodies as oncology therapeutics have been the introduction and approval of bevacizumab (Avastin), an anti-vascular endothelial growth factor antibody and of trastuzumab (Herceptin), an anti-human epidermal growth factor receptor 2 antibody and of cetuximab (Erbitux), an anti-epidermal growth factor receptor antibody. In current review, advances in antibody engineering, mechanisms of action of anti-cancer antibodies and trends in the clinical development of monoclonal antibodies for cancers are overviewed and future directions of research and development for this class of therapeutics are discussed.